Regional security cooperation reinvented: Western Balkans counterterrorism initiative. Issue 4 (2nd October 2018) - Đorđević, Vladimir; Klemenc, Jelka; Kolářová, Ivana
ABSTRACT: This article argues that the Western Balkans Counterterrorism Initiative (WBCTi), originally a Slovenian proposal of late 2014, represents an efficient form of regional security cooperation, particularly when regional EU integration is considered. The Initiative that was accepted by the Justice and Home Affairs Council of the EU in late 2015 is the first of its kind. It is aimed at both incorporating and integrating all forms of international assistance that concern increasing the capacity to prevent and combat terrorism, violent extremism, and radicalisation leading to terrorism. Additionally, it is directed at decreasing duplication of actions by international actors and raising levels of efficiency of security cooperation and reform. This article analyses the Initiative by focusing on its structure and claiming that its specific framework represents an innovative approach establishing a fully functional regional structure outlining EU-Western Balkans security cooperation.